Paradoxical bronchoconstriction caused by β2-adrenoceptor agonists - Khadija Ayed; Islam Latifa Hadi Khalifa; Salma Mokaddem; Saloua Ben Khamsa Jameleddine (AboutScience Srl, 2020)
Introduction: Salbutamol and terbutaline are short-acting β2 adrenergic agonists that produce bronchial smooth muscle relaxation and are widely used in obstructive pulmonary diseases. Nevertheless, their use has been the cause of a paradoxical bronchoconstriction, which is a rare and potentially serious adverse reaction. The aim of this study is to report a case of paradoxical bronchoconstriction caused by β2 adrenergic agonists. Methods: This case is about a 50-year-old asthmatic patient who describes a history of repeated acute asthma attacks after salbutamol inhalation or terbutaline nebulization. A double-blind crossover study was performed over 3 days, in order to compare the effects of each bronchodilator. Forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and maximal expiratory flow 25-75 (MEF25-75) were measured. Results: On the first day, a bronchoconstriction caused by deep and repeated inhalations was eliminated. On the second day, an airway obstruction was confirmed by a decrease in FEV1 at 40% from baseline values after nebulization of a standard dose of terbutaline. On the third day, a spirometry was performed before and after nebulization of a standard dose of ipratropium bromide, and there were no significant changes in the spirometric parameters. Finally the patient was discharged with a written warning mentioning the danger of salbutamol and terbutaline use. Conclusion: Salbutamol and terbutaline are generally well-tolerated β2 adrenergic agonists. Nevertheless, in rare cases, these substances can cause a paradoxical bronchoconstriction. Doctors must therefore remain vigilant about its side effect and possibly investigate each case.